489 A retrospective analysis of varying thresholds of baseline lung allograft dysfunction in bilateral lung transplant recipients - James McMenimen; Rodrigo Vazquez Guillamet; Ramsey Hachem; Jay Piccirillo; Tej Patel; Chad Witt (Journal of Clinical and Translational Science)
Objectives/Goals: Baseline lung allograft dysfunction (BLAD) is defined as the failure to attain normal lung function after transplant and has been associated with impaired survival. BLAD has no consensus definition and assessment of varying thresholds of abnormality may identify an impact on survival or development of chronic lung allograft dysfunction (CLAD). Methods/Study Population: This is a retrospective cohort analysis of bilateral lung transplant recipients who were transplanted between 1/1/2012 and 12/31/2022 who have complete pulmonary function data posttransplant. Thresholds of BLAD including percent predicted levels of FEV1 and FVC at 80%, 75%, 70%, 65%, and 60% were assessed. Outcomes evaluated include survival, development of CLAD, and association of key risk factors with the development of BLAD including donor, recipient, operative, and postoperative characteristics. Results/Anticipated Results: Totally, 680 bilateral lung transplant recipients were identified. Prevalence of BLAD ranged from 41.9% to 9.7% at specified thresholds. We anticipate performing survival analyses and evaluating development of CLAD in patients with BLAD at varying thresholds. We are assessing key donor, recipient, operative, and postoperative variables for association with BLAD. Preliminary analyses demonstrate significant associations of BLAD with recipient-donor height mismatch, prolonged mechanical ventilation time posttransplant, increased length of hospitalization posttransplant, the use of cardiopulmonary bypass intraoperatively and surgical allograft downsizing. Discussion/Significance of Impact: A threshold of BLAD at 70% predicted FEV1 and FVC or lower suggests importance for developing CLAD. Key characteristics associated with BLAD suggest importance of height mismatch, operative complexity, frailty, and severity of disease at time of transplant and immediately postoperatively.